Central Bank Transparency and Cross-Border Banking - Helge C. N. Littke; Stefan Eichler; Lena Tonzer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We analyze the effect of central bank transparency on cross-border bank activities. Based on a panel gravity model for cross-border bank claims for 21 home and 47 destination countries from 1998 to 2010, we find strong empirical evidence that central bank transparency in the destination country on average increases cross-border claims. Using interaction models, we find that the positive effect of central bank transparency on cross-border claims is only significant if the central bank is politically independent. Central bank transparency and credibility are thus considered as complements by banks investing abroad.
Keywords: E58; F30; G15; 330